Automatic calibration model of a building energy simulation using optimization algorithm. (May 2017) - Hong, Taehoon; Kim, Jimin; Jeong, Jaemin; Lee, Myeonghwi; Ji, Changyoon
Abstract: A lot of studies have been made to enhance the similarity between the target facility and building energy simulation (BES) model for an analysis of exact energy savings. Towards this end, ASHRAE guideline 14 presented the Coefficient of Variation of the Root Mean Square Error (CV(RMSE)) as criteria by which the similarity between the target facility and BES model can be measured. However, since the criteria of the CV(RSME) were met through manual and iterative performances in previous studies, this posed a disadvantage in that a lot of time and effort were consumed. In this regard, this study proposed an automatic calibration model for approaching the minimum CV(RMSE) using the BES model and optimization algorithm. The framework was conducted in five steps as follow: (i) collecting the target facility information; (ii) establishment of the BES model; (iii) calibration of the BES model in accordance with the CV(RMSE); (iv) setting the design variables and objective functions; (v) development of the automatic calibration model using optimization algorithm. As a result, the CV(RMSE) was automatically reduced from 18.10% to 12.62%. The proposed model improved calibration between actual energy data and simulation energy data while reducing time consuming.